Review article: acute severe ulcerative colitis – evidence‐based consensus statements. Issue 2 (26th May 2016) - Chen, J.‐H.; Andrews, J. M.; Kariyawasam, V.; Moran, N.; Gounder, P.; Collins, G.; Walsh, A. J.; Connor, S.; Lee, T. W. T.; Koh, C. E.; Chang, J.; Paramsothy, S.; et al.
Summary: Background: Acute severe ulcerative colitis (ASUC) is a potentially life‐threatening complication of ulcerative colitis. Aim: To develop consensus statements based on a systematic review of the literature of the management of ASUC to improve patient outcome. Methods: Following a literature review, the Delphi method was used to develop the consensus statements. A steering committee, based in Australia, generated the statements of interest. Three rounds of anonymous voting were carried out to achieve the final results. Acceptance of statements was pre‐determined by ≥80% votes in 'complete agreement' or 'agreement with minor reservation'. Results: Key recommendations include that patients with ASUC should be: hospitalised, undergo unprepared flexible sigmoidoscopy to assess severity and to exclude cytomegalovirus colitis, and be provided with venous thromboembolism prophylaxis and intravenous hydrocortisone 100 mg three or four times daily with close monitoring by a multidisciplinary team. Rescue therapy such as infliximab or ciclosporin should be started if insufficient response by day 3, and colectomy considered if no response to 7 days of rescue therapy or earlier if deterioration. With such an approach, it is expected that colectomy rate during admission will be below 30% and mortality less than 1% in specialist centres. Conclusion: These evidenced‐based consensus statements on acute severe ulcerative colitis, developed by a multidisciplinary group, provide up‐to‐date best practice recommendations that improve and harmonise management as well as provide auditable quality assessments.